2019
DOI: 10.1016/j.heliyon.2019.e01893
|View full text |Cite
|
Sign up to set email alerts
|

Recreational water quality status of the Kidd's Beach as determined by its physicochemical and bacteriological quality parameters

Abstract: Coastal water resources are habitually exposed to indiscriminate anthropogenic pollution. However, due to their negative consequences to the public health, recreational waters require continuous monitoring for disease-causing organisms as a way of preventing ailments associated with swimming. As a result, the present study assessed the physicochemical parameters and microbial loads of water samples collected from six different sampling points on Kidd's Beach using standard analytical procedures. Generated data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
2
7
0
2
Order By: Relevance
“…The TDS showed positive correlation with hydrocarbons in the surface water (r = 0.53∗) and sediment (r = -0.40). Similar to this study, the study of Adeniji et al. (2019) in Kidd's Beach (Cape Province) in South Africa found a positive correlation between the TDS and EC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The TDS showed positive correlation with hydrocarbons in the surface water (r = 0.53∗) and sediment (r = -0.40). Similar to this study, the study of Adeniji et al. (2019) in Kidd's Beach (Cape Province) in South Africa found a positive correlation between the TDS and EC.…”
Section: Discussionsupporting
confidence: 89%
“…The TDS showed positive correlation with hydrocarbons in the surface water (r ¼ 0.53*) and sediment (r ¼ -0.40). Similar to this study, the study of Adeniji et al (2019) in Kidd's Beach (Cape Province) in South Africa found a positive correlation between the TDS and EC. The negative correlation observed shows that, despite the increasing trend of TDS and EC downstream, TPH is reducing downstream.…”
Section: Compoundsupporting
confidence: 89%
“…Sobreviven sólo por cortos periodos de tiempo en el agua (Rubio-Arias et al 2016), por lo que sirven de alerta sobre la posible presencia de patógenos potenciales (WHO 2003, Gracia et al 2018. La alta prevalencia de especies de enterococos puede ser un indicador de posibles riesgos para la salud de los usuarios que frecuentan estas aguas (Adeniji et al 2019). Nevers et al (2018) estudiaron la densidad de Escherichia coli en aguas del lago Michigan (Indiana), concluyendo que el principal aporte de este microorganismo es por aves, seguido de perros y humanos.…”
Section: Caracterización Microbiológicaunclassified
“…Total genomic DNA was extracted using the boiling method as described by Magueri et al [39]. Confirmative PCR identification of enterococci was done based on the method described by Ke et al [40] and Adeniji et al [41] using genus-specific primers targeting the tuf-gene using E. faecalis (DSM 20,478) as a positive control.…”
Section: Dna Extraction and Pcr Confirmation Of Presumptive Enterococmentioning
confidence: 99%